COMMUNITY'S PERCEPTIONS AND ENTHUSIASM: EMPOWERING INFORMATION TECHNOLOGY AS MARKETING STRATEGY IN HOMECARE SERVICES - Yoyok Bekti Pasetyo; Kumboyono Kumboyono; Nina Septi Wardani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
enIntroduction: Community's Perception and enthusiasm toward homecare services becomes challenge to find out for homecare agency. An easy and effective strategy to find out is using technology information system. Methods: This study employed descriptive analysis design, in which perception and enthusiasm community were measured by completing questionnaire (r = 0.367 validity and reliability = 0.734–0.777), while data analysis uses correlation product moment and T-test. Results: Univariat analysis show perception toward homecare services within internal community results in:mean = 19.8; range 17–24, while within external community results in: mean = 19.53; range = 15–24. In other hand, enthusiasm toward homecare services within internal community results in: mean = 31.33; range= 28-36, while within external community results in: mean = 31.27; range = 26–36. Bivariat analysis result, first: Perceptions and enthusiasm internal community was associated toward homecare services (p = 0.001; r = 0.778). Second, Perceptions and enthusiasm external community was associated with homecare services (p = 0.010, r = 0.754). Thereby, no difference between internal community perception and external community perception toward homecare services (p = 0.778). Discussion: In conclusion, this study concludes that community's perception and enthusiasm was considered related to homecare services. This study provides information for homecare management that community needs homecare services to address health improvement among patients with chronic diseases.Keywords: community's perceptions and enthusiasm, homecare services, marketing strategy